Evaluation of Getar Thala Innovation Program (Gerakan Tanggulangi Anemia Remaja dan Thalassemia) during the Covid-19 Pandemic - Rabia Wahdah; Sulistyaningsih Sulistyaningsih; Herlin Fitriani Kurniawati (Universitas Aisyah Pringsewu, 2023)
Background: The GetarThala innovation program was doing by the Sleman District Health Office even during the Covid-19 pandemic. The coverage of the blood-added tablets for adolescent girls in 2019 was 81%, dropping to 37% in 2020. The research objective was to evaluate the implementation of the Getar Thala innovation program during the Covid-19 Pandemic in Sleman Regency. Methods: Qualitative research design with an embedded single case study. The selection of participants was using purposive sampling and the number of participants was 19 participants. Then, data collection used in-depth interviews from May to July 2022 and the analysis of data used thematic analysis. Results: There are 3 themes, namely input, process, and output indicators. Input indicators are human resources, program implementation facilities during the Covid-19 pandemic, structure of authority and responsibility for program implementers, financial resources and adolescent management. While the process indicators are program implementation, the blood-added tablets supplementation procedures, the obstacles to the blood-added tablets supplementation and program management during the Covid-19 pandemic. Then, the output indicators consist of the distribution coverage the blood-added tablets and the anemia rate of female adolescents. Conclusion: The implementation strategy was carried out by changing the target of female adolescents, changing the procedure for distributing the blood-added tablets, and obtaining an increase in the coverage of the blood-added tablets. Abstrak: Latar belakang: Program inovasi GeTarThala dilakukan oleh Dinas Kesehatan Sleman meski dalam kondisi pandemi Covid-19. Cakupan TTD (tablet tambah darah) remaja putri pada tahun 2019 sebanyak 81% melesat turun pada tahun 2020 yaitu sebanyak 37%. Tujuan penelitian adalah mengevaluasi implementasi program inovasi Getar Thala pada Masa Pandemi Covid-19 Di Kabupaten Sleman. Metode: Desain penelitian kualitatif dengan pendekatan embedded single case study. Pemilihan partisipan menggunakan purposive sampling, jumlah partisipan sebanyak 19 partisipan. Pengumpulan data menggunakan indepth interview pada bulan Mei sampai dengan Juli 2022. Analisis data menggunakan analisis tematik. Hasil: Didapatkan 3 tema yaitu indikator input, proses dan output. Indikator input yaitu SDM, fasilitas pelaksanaan program pada masa pandemi Covid-19, struktur wewenang dan tanggung jawab pelaksana program, financial resources dan pengelolaan remaja. Indikator proses yaitu pelaksanaan program, prosedur suplementasi tablet tambah darah, kendala suplementasi tablet tambah darah dan pengelolaan program di masa pandemi Covid-19. Indikator output terdiri dari cakupan distribusi tablet tambah darah dan angka anemia remaja putri. Kesimpulan: Strategi implementasi dilakukan dengan mengubah sasaran remaja puteri, perubahan prosedur distribusi tablet tambah darah, dan didapatkan peningkatan cakupan tablet tambah darah.